Некоторые организационно-правовые аспекты международного сотрудничества профсоюзных организаций Республики Беларусь и Китайской Народной Республики - Уздякин, Д. С. (БНТУ, 2015)
In this paper we study some organizational and legal aspects of international cooperation of trade unions of Republic of Belarus and the People's Republic of China at the present stage.